Resposta :
Resposta:
É só aplicar a fórmula de báskara ué
Explicação passo a passo:
[tex]b^2-4ac\\-b+-\sqrt{Delta}/2a[/tex]
Explicação passo-a-passo:
a) ∆= b²-4ac
∆= (-10)²-4*2*12
∆= 100 - 96
∆= 4
x= -b ± ✓∆/2a
x= - (-10) ± ✓4/2*2
x= 10 ± 2/4
x¹= 10+2/4 > 12/4 > 3
x²= 10 -2/4 > 8/4 > 2
b) ∆= (-10)² -4*5*5
∆= 100 - 100
∆= 0
x= -(-10) ±✓0/2*5
x= 10±0/10
x=1
c) ∆= (-6)²-4*1*5
∆= 36 -20
∆= 16
x= -(-6) ±✓16/2*1
x= 6±4/2
x¹= 6+4/2 > 10/2 > 5
x²= 6-4/2 > 2/2 > 1
d) ∆= 6² -4*(-1)*(-9)
∆= 36 - 36
∆=0
x= -6 ± ✓0/2*(-1)
x= -6/-2
x= 3